Design and Development of Poultry Disease Classification with Certainty Factor Method - Panji Palguna, I Gusti Agung Ngurah; Astuti, Luh Gede (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2020)
Expert systems in organizations aimed at adding value, increasing productivity and managerial areas that can draw conclusions quickly. Like with organizations that conduct livestock business that are very promising but necessary high vigilance against disease as well as highly poultry susceptible to various types of diseases caused by viruses or bacteria. To know the disease quickly made a system that is useful for detecting, so breeders can check their poultry without seeing a veterinarian for early detection. Permanent Veterinarian required for further treatment.